The Comparisons of Phenotypic and Genotypic Resistance of Staphylococcus aureus Isolates Against β-lactam and Tetracycline Antibiotics - Fatkhanuddin Aziz; Fauziah Fitriana; Dian Ritma Setyorini; Shafira Amalia Putri; Tifa Restyka Maulina; Vira Kartika Dewi; Nur Ika Prihanani; Morsid Andityas (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2023)
Staphylococcus aureus (S. aureus) is a Gram-positive bacteria that causes various diseases in humans and animals. Treatment of S. aureus infection generally uses antibiotics, but what happens is, S. aureus resistance to antimicrobial agents is an increasing global problem. This study aims to compare the phenotypic and genotypic characters of S. aureus from animals isolates against β-lactam and tetracycline antibiotics class. Determination of resistance characteristics of 8 S. aureus isolates was carried out phenotypically by Kirby Bauer and Minimum Inhibitory Concentration (MIC) methods, while genotypically by detecting the blaZ and tet genes. The results of the study showed a relationship between resistance genes and phenotypic test results using the Kirby Bauer and MIC methods. Isolates C, D, F, and TLK with resistance gene characters blaZ-, tetK-, and tetM- showed a sensitive interpretation of the results of the Kirby Bauer and MIC tests. On the other hand, DMG, J, PGT, and KRG isolates were resistant to one or two antibiotics tested, both phenotypic and genotypic (blaZ+, tetK+/tetM+). It found that the MIC levels of some respective isolates were relatively high, isolates J and KRG had an ampicillin MIC level of 32 μg/ml, while isolates J and PGT had 256 μg/ml for oxytetracycline. Although the identification of resistance genes and Kirby Bauer can determine the character of bacterial resistance, MIC determination is necessary to provide qualitative and quantitative information for the benefit of making therapeutic decisions and infection control strategies.